Strategies To Increase Employee Morale Of PT. Bineatama Kayone Lestari - Suwarli, Rifa Yulifah; Rahwana, Kusuma Agdhi; Wibawa, Gian Riksa (Journal of Management, Economic, and Accounting, 2024)
This research was conducted with the aim of determining the Effect of Occupational Safety and Health (K3) and Work Environment on Employee Work Spirit at PT. Bineatama Kayone Lestari. The method used in this study is a quantitative method using data obtained directly through questionnaires and distributed to 98 respondents who are employees of the polyester production department. The data analysis technique used in this study is multiple linear regression analysis. Based on the results of the study, it can be seen that Occupational Safety and Health (K3) and Work Environment simultaneously have a significant effect on employee work spirit. Occupational Safety and Health (K3) partially has a significant effect on employee work spirit. The Work Environment partially has a significant effect on employee work spirit.